FARMERS’ PERCEPTIONS OF RISK SOURCES AND RISK COPING STRATEGIES IN - A. Nazir; G. Li; M. J. Sheikh; X. Zhou; A. Humayoon; M. Rizwan; S. Akhtar (Journal of Animal and Plant Sciences, 2018)
Agricultural risks potentially decelerate the growth of a country and augment poverty level. For understanding farmers’ risk behavior and strategies to cope up possible related risks, the association to socioeconomic attributes, perceived risk sources and coping strategies were studied. A total of 480 farmers from the left bank of Indus River (Sindh Province of Pakistan) were interviewed using multistage cluster sampling method through valid and reliable means. Principal component analysis extracted 80% variations for both risk sources and risk coping strategies. While observing the effect of farmers’ demographic attributes on risk sources and coping strategies, change in agricultural machinery (Mean=4.25) for risk source, and promotion of products internationally (Mean=4.2) for management strategies were ranked the foremost. However, crop insurance, precautionary saving, off-farm activities and crop diversification were also found significant. From the Goodness-of-Fit indices of CFA, the RMSEA value for risk sources was 0.056 and 0.074 for risk coping strategies indicating that the measurement models are fit and within the required limits and considerably acceptable for a measurement model or structural model. Hence, the outcomes of this study may provide useful insight for policy makers, advisers, for decision making, developers and sellers of risk coping mechanisms. production, income, price and financial organizations
Keywords: Risk sources; Risk coping strategies; Factor analysis; EFA; CFA; Cronbach Alpha.